Role of papaya leaf juice in dengue fever - a case study - Anpuchelvi, S.; Sritharan, G. (Archers and Elevators Publishing House, 2019)
Dengue fever caused by dengue viruses having Aedes aegypti mosquito as their principal vector, causes symptoms such as sudden onset of fever, headache, retro- orbital pain and back pain along with severe myalgia due to which dengue fever is also known as "break-bone fever" laboratory findings include leucopenia, thrombocytopenia and in many cases, serum aminotransferase elevation. A pilot study and randomized controlled trial showed that administration of papaya leaf juice was beneficial in dengue patients in elevating the total white cell counts and platelet counts. Based on this report, a suspected dengue patient with thrombocytopenia and leucopenia was treated in a Siddha, Ayurveda Hospital. The patients were administered papaya leaf juice in the dose of 15 ml thrice daily along with conventional line of management for a period of seven days. There was remarkable improvement in the subjective symptoms and white blood cell and platelet count were restored to normalcy.
Keywords: Dengue fever; Papaya leaf juice; Platelet count